Epidemiology of Taenia solium cysticercosis in the pig value chain in Uganda - Kungu, Joseph M. (Makerere University, 2015)
A study was conducted in Kampala district, Uganda to map the distribution of pork retail outlets as well as assess their role in food borne disease transmission. This was the first study to map pork retail outlets and their hygiene in Kampala, a city considered to be a major destination for pigs from different parts of the country. We identified pork outlets by traversing major routes and by asking each outlet encountered about the location of others. Pork outlets were geo-referenced and mapped. Using a structured questionnaire, practices associated with hygiene related to infrastructure (e.g. water, refrigeration), workers (e.g. cleanliness, uniforms), and equipment (e.g. presence, condition) were assessed. Sources of pork were assessed to determine whether pork had undergone inspection, as were socio economic determinants of hygiene outcomes (e.g. gender and years of business operation) and risk factors for foodborne disease (consumption of salads and alcohol) There were 158 pork outlets in the five divisions of Kampala with the highest number (42) in Makindye division. Overall, 68% of the pork eaten in Kampala is from places where slaughtering was not authorized (un-gazetted) and meat inspection not carried out. The overall average hygiene score was 61% with considerable variation between districts. Worker hygiene score was highest (average 71%), followed by infrastructure (68.2%) and equipment (47.3%). There was a significant relation between good hygiene and the presence of a public health certificate (present only in 42% of the outlets). Although some aspects of hygiene in pork retail outlets are good, there is also room for improvement. The lack of meat inspection for most pork presents a risk. Having a public health certificate is an important predictor of good practices.